COVID-19 Reinfection: A review of the new evidence (Research, Society and Development, 2021)
The outbreak of the disease caused by the new coronavirus in 2019 (COVID-19) began in December 2019 and quickly spread across the world as a major health threat. Several reports of positive cases after hospital discharge have drawn research attention around the world. Thus, the present study seeks to report the main results of the most evidences scientific evidence regarding the theme. To this end, a narrative review was carried out using the main databases contained in the Virtual Health Library, a saber, Medical Literature Analysis and Retrieval System Online - MEDLINE and Latin American and Caribbean Literature in Health Sciences - LILACS. The short duration of seropositivity for neutralizing antibodies, the presence of more than genotypic variants of the virus, in addition to the fact that immunoglobulin levels may not correlate with viral elimination and the risk of SARS-CoV-2 transmissibility increase the risk of reinfection by viruses, making it extremely necessary to disseminate measures to prevent infection, until more aspects of the virus are known and there is an effective vaccine capable of promoting colletive immunity.